2021
DOI: 10.1002/chem.202101705
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Initiated Cobalt‐Catalyzed Radical Olefin Hydrogenation

Abstract: Outer‐sphere radical hydrogenation of olefins proceeds via stepwise hydrogen atom transfer (HAT) from transition metal hydride species to the substrate. Typical catalysts exhibit M−H bonds that are either too weak to efficiently activate H2 or too strong to reduce unactivated olefins. This contribution evaluates an alternative approach, that starts from a square‐planar cobalt(II) hydride complex. Photoactivation results in Co−H bond homolysis. The three‐coordinate cobalt(I) photoproduct binds H2 to give a dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 131 publications
1
13
0
1
Order By: Relevance
“…Indeed, HAT to benzene is consistent with the excited state of 2H + undergoing Ni–H homolysis to form free or solvated H • . These findings parallel those from a recent report from Schneider et al where H/D exchange was observed between a cobalt hydride and C 6 D 6 . Few examples of light-induced homolysis of a M–H bond to form free H • have been proposed. …”
Section: Results and Discussionsupporting
confidence: 88%
“…Indeed, HAT to benzene is consistent with the excited state of 2H + undergoing Ni–H homolysis to form free or solvated H • . These findings parallel those from a recent report from Schneider et al where H/D exchange was observed between a cobalt hydride and C 6 D 6 . Few examples of light-induced homolysis of a M–H bond to form free H • have been proposed. …”
Section: Results and Discussionsupporting
confidence: 88%
“…Specifically, we sought to investigate whether Co DHP complexes were viable hydrogenation catalysts and, if so, whether the DHP ligand would enable alternative mechanisms to more canonical organometallic pathways. 12 14 Here, we present a series of t Bu,Tol DHP Co catalysts that mediate olefin hydrogenation via a ligand-assisted hydrogenation pathway. Catalysis occurs efficiently under mild conditions, comparable with the best Co hydrogenation catalysts currently known.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Co features prominently among first-row transition metals in hydrogenation catalysis. Unlike Rh and Ir, Co does not necessarily proceed through classical two-electron transformations and, as with other first-row transition metals, exhibits a propensity for single-electron steps and varied spin states. These alternative trends can also be leveraged to obtain altered reactivity. For instance, recent reports have illustrated how Co complexes with ligands that can store protons or electrons can efficiently mediate catalytic hydrogenations, with some examples exhibiting alternative mechanistic pathways in the presence of light (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…46 Nevertheless, it is wellknown that cobalt hydride complexes can undergo HAT to alkenes, and recently showed that it can be photoinduced. 35,66 We noted that the yield of the reductive homocoupling product decreased with the alkyl substituent size at the olefin (from -Me to i Pr), suggesting that steric effect of the substituent influences the product selectivity, as expected for radical couplings. Moreover, the conversion of the -Me, -Et substituted alkenes (28, 29) was quantitative but not for the one with the i Pr group (30).…”
Section: (Ii) Scope Of the Reactionmentioning
confidence: 83%
“…46 Nevertheless, it is well-known that cobalt hydride complexes can undergo HAT to alkenes, and it was recently shown that it can be photo-induced. 35,66…”
Section: Resultsmentioning
confidence: 99%